#### Answer

$\frac{y^{10}}{9x^8}$

#### Work Step by Step

$(3x^4y^{-5})^{-2}=3^{-2}(x^4)^{-2}(y^{-5})^{-2}=\frac{1}{9}x^{-8}y^{10}=\frac{y^{10}}{9x^8}$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$\frac{y^{10}}{9x^8}$

$(3x^4y^{-5})^{-2}=3^{-2}(x^4)^{-2}(y^{-5})^{-2}=\frac{1}{9}x^{-8}y^{10}=\frac{y^{10}}{9x^8}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.